THEORETICAL ASPECTS OF FORMING ECOLOGICAL CULTURE OF FUTURE SPECIALISTS IN MEDICAL COLLEGES (Innovative professional education, 2024)
The section examines the importance of forming the environmental culture of future specialists as a component of their professional training. In addition to biologicalaspects, emphasis is placed on moral and spiritual values and the «ecology of culture». The importance of ecological consciousness and harmonious relations between man and nature, which are critically important in the conditions of the global ecological crisis, is emphasized. Special attention is paid to fostering a responsible attitude towards the environment as a basis for the sustainable development of society.
Keywords: ecological culture, moral and spiritual values, cultural ecology, ecological consciousness, professional training, sustainable development